Pembersihan Sumur Gas Pada Produksi Gas Alam: Cleaning Of Gas Wells in Natural Gas Production - Agus Ardianto Budiman; Nurul Magfirah; Jamal Rauf Husain (CV Insight Publisher, 2023)
Natural gas is an alternative energy source in current industrial development, so the demand for natural gas is increasing. The purpose of this research is to activate the function of the well so that it can resume production. The healthy cleaning method used is the clean-up method. This method is a method of removing pressure shut-off fluid in wells by using chokes of various sizes. The type of choke used is a fixed choke. The completeness of the data used is in the form of well testing data on the well, gas composition, and the amount of dead liquid included as a comparison. From the results of research on each well, it is known that in the Walanga#1 well, with 30 barrels of liquid raised and a pressure of 1,080 psi, Walanga#2, with 14 barrels of liquid lifted and a force of 1,080 psi, Walanga#3 with 38 barrels of liquid lifted and a pressure of 1,078 psi, Sampi-sampi # 1 with 80 barrels of liquid raised and a pressure of 1,050 psi. Therefore, based on the results of this study, it can be concluded that the dead liquid was not lifted to its maximum. Still, the pressure in the wells had reached its maximum value and returned to normal conditions so that the four wells could resume production.